PENGARUH MACROMEDIA FLASH TERHADAP PEMAHAMAN KONSEP MATEMATIKA - Junar Syarif Pudin (Bajang Institute, 2023)
This study aims to determine the effect of Macromedia flash on the understanding of mathematical concepts. This experimental research was conducted at SMP PGRI 20 JAKARTA in the academic year 2016/2017. Research sample taken with random this class, obtained class VII-2 as experiment class and class VII-3 as control class. Research data from each class is obtained by posttest of the instrument in the form of 10 items about the form of description by fulfilling the assessment aspect for the concept comprehension ability. The instruments used in this study have been tested in advance and all items are valid and have a high degree of reliability. Data analysis of research result using t test, by first testing the assumption of normality and homogeneity. The results showed that there is a significant effect of Macromedia Flash on the understanding of mathematical concepts, especially in triangle and quadrilateral materials in class VII SMP PGRI 20 JAKARTA.